HUBUNGAN TINGKAT PENGETAHUAN PENGAWAS MENELAN OBAT (PMO) DENGAN KEBERHASILAN PENGOBATAN TUBERCULOSIS (TB) PARU - Manurung, Mian; Nurchayati, Sofiana; Woferst, Rismadefi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Supervisor Swallowing Medicine was important role in increased medication adherence. The family was closest unit to the patient and biggest motivator for treatment behavior of patients with pulmonary TB. The attention and supported Supervisor Swallowing Medicine family in supervising and reminding suffered to take medicine can improved degree of patient compliance. This can be influenced by Supervisor Swallowing Medicine knowledge of pulmonary TB and counseling families. This studied aims to determine the relationship level of Supervisor Swallowing Medicine knowledge with the success of pulmonary TB treatment in the area Harapan Raya Health Center Pekanbaru Work Area. The studied used quantitative approached with a descriptive retrospective correlation research design. Research activitied began from August-December 2019. The measuring instrument used was a questionnaire that had been tested for validity and reliability. The researched sample was Supervisor Swallowing Medicine of TB patients in the working area of Harapan Raya Health Center as many as 30 respondents. Bivariate resulted obtained from 30 respondents data obtained 24 respondents (80%) have high Supervisor Swallowing Medicine knowledge and 6 respondents (20%) have low Supervisor Swallowing Medicine knowledge. Of the 24 respondents who had high Supervisor Swallowing Medicine knowledge, there were 24 respondents (100%) who were successful in the treatment of pulmonary TB, while from 6 respondents who had low Supervisor Swallowing Medicine knowledge there were 3 respondents (50%) who were not successful in the treatment of pulmonary TB. The results of bivariate analysis with chi square obtained p value = 0,000 <(Î± = 0.005), concluded that there was a relationship between the level of Supervisor Swallowing Medicine knowledge and the success of pulmonary TB treatment in the working area of the Harapan Raya Health Center in Pekanbaru. It is recommended to nurses to provide health education to improve Supervisor Swallowing Medicine knowledge. Keywords: Knowledge, Success of Pulmonary TB Treatment, Supervisor Swallowing Medicine, Tuberculosis